Understanding Factors Associated with Quality of Life in Patients with Venous Thromboembolism - Erickson, Reaghan M.; Feehan, Michael; Munger, Mark A.; Tak, Casey; Witt, Daniel M. (Thrombosis and Haemostasis, 2019)
Introduction Quality of life (QoL) deficits have been noted among patients with venous thromboembolism (VTE) but understanding of the drivers of that poorer QoL is limited. The objective of this study was to examine associations between a variety of factors and QoL in patients with VTE.Methods Adult patients who had experienced at least one VTE episode within the past 2 years completed an online survey between May and July 2016 with responses to a variety of questions designed to ascertain QoL scores, Optum Short Form-12, and potential factors associated with these scores.Results Most of the 907 patients were female (56.7%) and Caucasian (88.6%). Physical and mental QoL scores below the general population average were present in 76.0 and 56.7% of patients, respectively. Multiple regression modeling revealed several factors associated with below average physical QoL scores including unemployment (odds ratio [OR] 3.77, 95% confidence interval [CI] 1.76–8.05), gastrointestinal bleeding (OR 2.54, 95% CI 1.28–5.01), high depression scores (OR 4.02, 95% CI 1.88–8.58), or difficulty accessing VTE care (OR 4.24, 95% CI 1.77–10.17). Factors associated with below average mental QoL scores included experiencing VTE within the last month (OR 3.85, 95% CI 1.58–9.41), unemployment (OR 2.83, 95% CI 1.30–6.16), or high depression (OR 3.85, 95% CI 1.60–9.28) and/or anxiety (OR 9.17, 95% CI 4.81–17.47) scores.Conclusion Most patients with recently diagnosed VTE reported below average QoL. Many of the factors associated with below average QoL are modifiable, indicating that patients with VTE could potentially benefit from interventions aimed at improving QoL.
Keywords: venous thromboembolism; quality of life; bleeding; anxiety; depression